2019
DOI: 10.3389/fnbeh.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress Induces Schizophrenia-Like Behavior in Mice With Reduced MMP-9 Activity

Abstract: Understanding gene-environment interactions in the pathogenesis of schizophrenia remains a major research challenge. Matrix metalloproteinase-9 (MMP-9) has been previously implicated in the pathophysiology of schizophrenia. In the present study, adolescent Mmp-9 heterozygous mice, with a genetically lower level of MMP-9, were subjected to resident-intruder psychosocial stress for 3 weeks and then examined in behavioral tests that evaluated cognitive deficits and positive- and negative-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Present world scenario places a large population of adolescent individuals (10-20%) at risk, particularly in the developing world, with most being underdiagnosed and under-treated leading to growing cases of depression and suicide (Kessler et al 2007). In our previous work (Vafadari and Mitra et al 2019) we had reported that wild-type mice that underwent adolescence psychosocial stress exhibited increased locomotion in open field and after treatment with MK-801 providing evidence for behavioral implications of the stress paradigm. We had further shown that reduced levels of synaptic, extracellularly-operating matrix metalloproteinase-9 (MMP-9) known to affect dendritic spine morphology (Michaluk et al, 2011), further accentuates the phenotype and leads to schizophrenia like symptoms (Vafadari and Mitra et al 2019).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Present world scenario places a large population of adolescent individuals (10-20%) at risk, particularly in the developing world, with most being underdiagnosed and under-treated leading to growing cases of depression and suicide (Kessler et al 2007). In our previous work (Vafadari and Mitra et al 2019) we had reported that wild-type mice that underwent adolescence psychosocial stress exhibited increased locomotion in open field and after treatment with MK-801 providing evidence for behavioral implications of the stress paradigm. We had further shown that reduced levels of synaptic, extracellularly-operating matrix metalloproteinase-9 (MMP-9) known to affect dendritic spine morphology (Michaluk et al, 2011), further accentuates the phenotype and leads to schizophrenia like symptoms (Vafadari and Mitra et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…In our previous work (Vafadari and Mitra et al 2019) we had reported that wild-type mice that underwent adolescence psychosocial stress exhibited increased locomotion in open field and after treatment with MK-801 providing evidence for behavioral implications of the stress paradigm. We had further shown that reduced levels of synaptic, extracellularly-operating matrix metalloproteinase-9 (MMP-9) known to affect dendritic spine morphology (Michaluk et al, 2011), further accentuates the phenotype and leads to schizophrenia like symptoms (Vafadari and Mitra et al 2019). Hence, we investigated whether there are any long-term structural changes in wild-type mice due to stress that might have acted as a pre-cursor to the behavioral changes and gene x environment (GXE) affects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our knowledge in the basic and clinical pathophysiology of neuropsychiatric diseases, such as schizophrenia, is still limited. “Schizophrenia is a severe neuropsychiatric disease that is characterized by impairments in perception, cognition, and avolition, leading to positive, cognitive, and negative symptoms, respectively” [ 3 ]. The etiology of schizophrenia remains unknown [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor is stress. Stress can induce changes in the gut microbiome [ 7 ] and it is well known that stress is one of the risk factors for the pathogenesis of schizophrenia [ 3 , 8 , 9 , 10 , 11 ]. Finally, several lines of evidence support the notion that gut microbiota can affect stress-related behaviors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%